Analisis Profil Metabolit Ekstrak Etanol Gracilaria verrucosa Menggunakan Liquid Chromatography–High Resolution Mass Spectrometry - Ningrum, Andriani Noerlita; Hasanah, Yesi Ihdina Fityatal (LPPM Institut Pendidikan Nusantara Global, 2025)
Gracilaria verrucosa is a red alga with promising potential as a source of bioactive metabolites. Previous studies have mainly reported antioxidant or antibacterial activity and total phenolic content without resolving specific molecular entities. This study aimed to generate a non-targeted LC–HRMS profile of semi-polar secondary metabolites from the ethanol extract of G. verrucosa and to annotate dominant ion features into defined chemical classes. Dried biomass was macerated with 96% ethanol and analysed using UHPLC–Orbitrap HRMS in Full MS/dd-MS² mode. After QC filtering, 325 ion features were detected; 51 could be annotated with Schymanski level 2–3 confidence into five classes: oxylipins/jasmonate derivatives, phytosterols, ionone-type apocarotenoids, phenolic–flavonoids, and carnitine-conjugated lipids. Representative candidates included jasmonic acid, 6-hydroxy-3-oxo-α-ionone, cholesteryl triol, flavonoid derivatives, and eicosadienoylcarnitine. These results indicate that the semi-polar metabolome of G. verrucosa is enriched in signalling-related oxylipins and sterols, antioxidant phenolic scaffolds, and acylcarnitines linked to energy metabolism, thereby providing a more mechanistic basis for its reported bioactivities. To our knowledge, this is the first comprehensive LC–HRMS-based metabolite map of Indonesian G. verrucosa, and it offers a chemically resolved framework to support subsequent fractionation, isolation, structural elucidation, and targeted pharmacological studies.